Reducing Child Malnutrition : How Far Does Income Growth Take Us? - Haddad, Lawrence; Alderman, Harold; Appleton, Simon; Song, Lina; Yohannes, Yisehac (Washington, DC: World Bank, 2014)
How rapidly will child malnutrition respond to income growth? This article explores that question using household survey data from 12 countries as well as data on malnutrition rates in a cross-section of countries since the 1970s. Both forms of analysis yield similar results. Increases in income at the household and national levels imply similar rates of reduction in malnutrition. Using these estimates and better than historical income growth rates, the article finds that the millennium development goal of halving the prevalence of underweight children by 2015 is unlikely to be met through income growth alone. What is needed to accelerate reductions in malnutrition is a balanced strategy of income growth and investment in more direct interventions.